2011
DOI: 10.1016/j.jacc.2010.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia–Associated Mutations From Background Genetic Noise

Abstract: This study is the first to comprehensively evaluate genetic variation in healthy controls for the ARVC susceptibility genes. Radical mutations are high-probability ARVC-associated mutations, whereas rare missense mutations should be interpreted in the context of race and ethnicity, mutation location, and sequence conservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
214
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(228 citation statements)
references
References 24 publications
8
214
2
4
Order By: Relevance
“…On average, the mutation detection rate for the most common ARVC-related genes are: PKP2 11-51%, DSG2 3-20%, DSC2 1-7%, JUP 0.5-16% and DSP 1-7%. 5,12,13,[17][18][19][20][21] …”
Section: Clinical Sensitivity (Proportion Of Positive Tests If the DImentioning
confidence: 99%
“…On average, the mutation detection rate for the most common ARVC-related genes are: PKP2 11-51%, DSG2 3-20%, DSC2 1-7%, JUP 0.5-16% and DSP 1-7%. 5,12,13,[17][18][19][20][21] …”
Section: Clinical Sensitivity (Proportion Of Positive Tests If the DImentioning
confidence: 99%
“…For example, Fressart et al [18] included AC patients from Hispanic, Maghreb and Caribbean origin. Interesting in this respect are the findings of a recent study by Kapplinger et al [12], where it was shown that in the control population in the absence of heart disease manifestation, DNA variant prevalence in desmosomal protein encoding genes was approximately threefold lower in Caucasians than in non-Caucasians. However, so-called 'radical mutations' which are most likely associated with an AC phenotype showed a very low prevalence in both Caucasian (0%) and non-Caucasian (0.6%) controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, so-called 'radical mutations' which are most likely associated with an AC phenotype showed a very low prevalence in both Caucasian (0%) and non-Caucasian (0.6%) controls. Finally, radical mutations, defined by the authors as insertions, deletions, splice junction or nonsense mutations, constitute the majority of genetic alterations in so-called mutation-positive AC patients, while many of the missense mutations found in controls and patients most likely have no causal effect with AC [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that stop-coding in diseasecausing genes are more pathogenic than missense mutations, since the former are causing alteration of protein length and conformation, leading to haploinsufficiency due to protein instability [67][68][69][70]. Entire PKP2 exons or even whole gene deletions have been recently described in AC families with a frequency of approximately 2 % [71][72][73].…”
Section: Ac Genes/mutations and Diagnostic Implicationsmentioning
confidence: 99%